FACTORS ASSOCIATED WITH HEALTH LITERACY - Maricic, Milena; Radovanovic, Snezana; Gavrilovic, Ivana; Jevtović Obradović, Ivana; Кhouitar, Samir; Mujkovic, Marija (HEALTH CARE, 2020)
The World Health Organization defines health literacy as cognitive and social skills and the capacity to access, understand and use information in a way that promotes and protects human health. People who have higher levels of health literacy are more responsible for their health, family health and the health of their community. Healthcare professionals and researchers, as well as health policy makers, have recognized the need to focus on health literacy as a possible factor in reducing health disparities. However, the precise nature of the relationship between health literacy and the factors that determine it, is still rather unclear.
Keywords: Health literacy, health disparities, public health